Development of innovative e-module on team-based method to improve collaboration skills - Kusumantoro Kusumantoro; Kemal Budi Mulyono; M. Fathur Rahman; Norzaidi Mohd Daud (JINoP (Jurnal Inovasi Pembelajaran), 2023)
Nowadays, the demand for collaborative skills is a fundamental element in learning. However, many teaching materials and modules do not yet accommodate these skills. This research aims to develop an innovative e-module based on the team-based method to enhance students' learning outcomes and collaborative skills in the course of Indonesian Economics. This research follows the Research and Development (R&D) approach using the ADDIE model, with data collection instruments including a needs analysis questionnaire, an expert evaluation scale for the e-module's content and media, a self-directed learning scale, and a student response scale, which were subsequently analyzed descriptively. The research results indicate that, based on assessments from content experts, media experts, and practitioners, the e-module is considered highly suitable. The effectiveness testing results demonstrate that the innovative e-module based on the team-based method significantly enhances students' learning outcomes and collaborative skills. As an implication, instructors of the Indonesian Economics course are encouraged to implement this e-module while considering the characteristics of the students they are teaching.